Association between liver steatosis and angiogenesis in chronic hepatitis C - Kukla, Michał; Gabriel, Andrzej; Sabat, Daniel; Liszka, Łukasz; Wilk, Mariusz; Petelenz, Michał; Musialik, Joanna; Dzindziora-Frelich, Iwona (Polish Journal of Pathology, 2010)
Background : The relationship between steatosis and angiogenesis in chronic hepatitis C (CHC) is unclear. Aim and methods : The aim was to explain whether liver steatosis presence and its extent are associated with the number of new-formed blood vessels in lobules and portal tracts in CHC. 72 CHC patients infected with viral genotype 1b, 35 of whom had steatosis were evaluated. Monoclonal antibody anti-CD34 was used to identify new-formed blood vessels. Results : Patients with steatosis had a significantly more advanced stage of fibrosis (p = 0.002) and higher inflammatory activity grade (p = 0.062). CD34 expression in portal tracts (CD34pt), lobules and fibrous septa (CD34lfs) and total (CD34) were significantly higher in patients with steatosis (p = 0.034; p = 0.021; p = 0.023, respectively). CD34, CD34pt and CD34lfs differed significantly between patients with various steatosis grade (p = 0.006; p = 0.009; p = 0.013, respectively). CD34 and CD34pt differed significantly between each steatosis grade whereas CD34lfs between grade 1 and 3. Fibrosis stage and inflammatory grade were positively associated with steatosis extent (p = 0.015; p = 0.003, respectively). Conclusions : Our observations suggest that extensive steatosis of liver parenchyma in CHC patients is associated with formation of new blood vessels in lobules and portal tracts. Understanding the relationship between steatosis, fibrosis and angiogenesis is therefore of great importance for the introduction of new therapeutic approaches and in the evaluation of CHC progression.